(untitled) (Journal of the Sylhet Agricultural University, 2025)
The sea beach is the most visually appealing and popular tourist destination in Bangladesh, and it makes a significant economic contribution to both the local and national economies. But this coastal water is polluting with solid and liquid water which discharge directly or indirectly through land wash or drainage system to the coastal water of Cox’s Bazar. This waste and waste water carry excess nutrient and pathogenic microbe and pollute coastal water. For that this study was conducted at Teknaf, Himchori, Kolatoli, Laboni, Bakkhali sites of Cox’s Bazar Districts to understand the status and relation of nutrients and microbial load and coastal water pollution which is very important for tourism, health and safety. For sampling, preservation and analysis APHA (1999) methods were followed. According to the study, the microbial load was too high for swimming and bathing. There was some significant relation among nutrient, seasons and microbes in the study areas. In Premonsoon, the highest level of Total Viable Count (TVC) had shown at Bakkhali site (336 cfu/ml) and lowest level of Total Viable Count (TVC) had shown at Himchary site (116 cfu/ml) whereas the, standard value of TVC was only 10 cfu/ml. Noticeably, the standard value of Faecal coliform and streptococcus was simply 1 cfu/ml but our received results from different five sites were exceptionally high. However, in case of pathogenic bacteria Salmonella and Vibrio the standard value was 2.7 cfu/ml and 7 cfu/ml respectively. The fascinating information was that, the Laboni (0 cfu/ml) and Himchary (2 cfu/ml) site had shown less number of Salmonella than the standard value (2.7 cfu/ml). In addition, Kolatoli (1 cfu/ml) and Laboni (6 cfu/ml) site had shown less number of Vibrio than standard value (7 cfu/ml). In Monsoon, it also shown immense deviation. Especially at Himchary site, TVC (764 cfu/ml) and Steptococcus (761cfu/ml) were noted. On the other hand, Kolatoli site had demonstrated highest number of Fecal Coliform (258 cfu/ml) and Salmonella (104 cfu/ml). But in Postmonsoon it had represented the greatest deviation from standard data. Among the three season, the higher level of Total Viable Count (TVC), Fecal Coliform, Salmonella, Vibrio Chlorella, Streptococcus had shown at all the sites in Monsoon season and lower level of Total Viable Count (TVC) had shown in Pre monsoon and Post monsoon. In respect of nutrient NH4-N, NO2-N, SiO3-Si were higher in Monsoon but PO4-P value were lower in Monsoon and higher in Pre monsoon and Post monsoon. J. Sylhet Agril. Univ. 12(1): 58-71, 2025